Simulation of water flushing in an enclosure - Koh, Jason Ming Jun. (2013)
This report seeks to explore the interactions of water flow with respect to air and the enclosure walls using computer simulation tools and appropriate turbulent models of CFD commercial software. The purpose of this study is thus to simulate a realistic model which can thus be used to study the influence of various factors on the efficiency of flushing.